2023
DOI: 10.3389/fimmu.2023.1254911
|View full text |Cite
|
Sign up to set email alerts
|

Novel Siglec-15-Sia axis inhibitor leads to colorectal cancer cell death by targeting miR-6715b-3p and oncogenes

Mohammed Saqif Ahmad,
Maria Braoudaki,
Hershna Patel
et al.

Abstract: Siglecs are well known immunotherapeutic targets in cancer. Current checkpoint inhibitors have exhibited limited efficacy, prompting a need for novel therapeutics for targets such as Siglec-15. Presently, small molecule inhibitors targeting Siglec-15 are not explored alongside characterised regulatory mechanisms involving microRNAs in CRC progression. Therefore, a small molecule inhibitor to target Siglec-15 was elucidated in vitro and microRNA mediated inhibitor effects were investigated. Our research finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Beta-amino carbonyl derivatives have demonstrated promising potential in medicinal chemistry, drug development, and cancer therapy owing to their diverse biological activities and capacity to trigger apoptosis in cancerous cells. , This research incorporated an eco-friendly approach in an efficient, simple, and green catalytic process to produce SHG-8, aiming to demonstrate its in vitro cytotoxic effects on GB cell models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beta-amino carbonyl derivatives have demonstrated promising potential in medicinal chemistry, drug development, and cancer therapy owing to their diverse biological activities and capacity to trigger apoptosis in cancerous cells. , This research incorporated an eco-friendly approach in an efficient, simple, and green catalytic process to produce SHG-8, aiming to demonstrate its in vitro cytotoxic effects on GB cell models.…”
Section: Resultsmentioning
confidence: 99%
“…Similar cytotoxic effects were previously observed with several β-AC compounds on human prostate cancer cells and colorectal cancer cells. 20 , 21 Currently, the most effective drug against gliomas is the chemotherapeutic agent TMZ. Combining chemotherapy with TMZ and radiotherapy is considered a gold standard therapeutic approach incorporated in the treatment regimens of GB patients with surgical tumor excision.…”
Section: Resultsmentioning
confidence: 99%
“…A large amount of evidence suggests that SIGLECs receptors hold promise as novel immune checkpoints and attractive targets for cancer immunotherapy ( Lim et al, 2021 ; Stanczak et al, 2023 ). Research suggests that combining SIGLEC15 with PD-L1 antagonists holds promise for treating colorectal cancer ( Ahmad et al, 2023 ). SIGLEC7 is implicated in modulating the immune response to Fusobacterium nucleatum in colorectal cancer ( Lamprinaki et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Several reviews, including our recently published one discussing the significance of molecular hybrids in cancer treatment, are available in the literature. 18,33–37 The pharmacological relevance of hybrids and our experience in the field of cancer 38–43 and tamoxifen 1,44 motivated us to compile the review on tamoxifen hybrids and discuss their application in cancer treatment. This review compiles the recently reported covalently linked organometallic, fluorescent, photocaged, nanoparticle, and novel ligand-based tamoxifen hybrids and discusses their design strategies, chemical structure, and pharmacological profile.…”
Section: Introductionmentioning
confidence: 99%